Biochemical Characterization of an Extracellular β-Glucosidase from the Fungus, Penicillium italicum, Isolated from Rotten Citrus Peel - Park, Ah-Reum (The Korean Society of Mycology, 2012)
A β-glucosidase from Penicillium italicum was purified with a specific activity of 61.8 U/mg, using a chromatography system. The native form of the enzyme was an 88.5-kDa tetramer with a molecular mass of 354 kDa. Optimum activity was observed at pH 4.5 and 60℃, and the half-lives were 1,737, 330, 34, and 1 hr at 50, 55, 60, and 65℃, respectively. Its activity was inhibited by 47% by 5 mM Ni(2+). The enzyme exhibited hydrolytic activity for p-nitrophenyl-β-D-glucopyranoside (pNP-Glu), p-nitrophenyl-β-D-cellobioside, p-nitrophenyl-β-D-xyloside, and cellobiose, however, no activity was observed for p-nitrophenyl-β-D-lactopyranoside, p-nitrophenyl-β-D-galactopyranoside, carboxymetyl cellulose, xylan, and cellulose, indicating that the enzyme was a β-glucosidase. The k(cat)/K(m) (s(-1) mM(-1)) values for pNP-Glu and cellobiose were 15,770.4 mM and 6,361.4 mM, respectively. These values were the highest reported for β-glucosidases. Non-competitive inhibition of the enzyme by both glucose (K(i) = 8.9 mM) and glucono-δ-lactone (K(i) = 11.3 mM) was observed when pNP-Glu was used as the substrate. This is the first report of non-competitive inhibition of β-glucosidase by glucose and glucono-δ-lactone.